Biosurfactants: Production and potential applications in microbial enhanced oil recovery (MEOR). (April 2018) - S.J., Geetha; Banat, Ibrahim M.; Joshi, Sanket J.
Abstract: Microbial enhanced oil recovery (MEOR) is a type of enhanced oil recovery (EOR) technology, generally employed as a tertiary stage where oil recovery using primary and secondary traditional methods is not feasible anymore. Amongst several potential biological agents useful for MEOR, biosurfactants (biologically produced amphiphilic surfactants) play key roles. They are mostly equivalent to or better than their chemical counterparts in several aspects including; better environmental compatibility, production from renewable waste substrates, maintaining activity at harsh environmental conditions, lower or no environmental toxicity. Biosurfactants are still not cost-competitive when compared to chemical surfactants. Different strategies like the use of cheaper raw materials, optimization of media components, fermentation processes and downstream processes, use of hyperproducers are currently explored to improve biosurfactant production economics. Biosurfactant mediated MEOR (BS-MEOR) could be applied by either in-situ or ex-situ techniques. In-situ BS-MEOR could be applied by injecting biosurfactant producing microorganisms in the oil well with or without additional nutrients. Generally followed by shut-in phase and subsequently monitoring microbial activities, metabolites production and oil recovery from the producer wells. Whereas for ex-situ BS-MEOR applications, the biosurfactant is produced outside the oil well and injected directly for enhancing oil recovery. This review highlights the biosurfactant production and economics, general protocols for applications from lab-to-field scale, different successful trials along with pros and cons of both in-situ and ex-situ BS-MEOR applications.